2018
DOI: 10.1016/j.jses.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Readability assessment of American Shoulder and Elbow Surgeons patient brochures with suggestions for improvement

Abstract: BackgroundMany Americans have limited literacy skills, and the National Institutes of Health (NIH) suggests patient educational material be written below the 8th grade level. Many orthopedic organizations provide print material for patients, but whether these documents are written at an appropriate reading level is not clear. This study assessed the readability of patient education brochures provided by the American Shoulder and Elbow Surgeons (ASES).Materials and MethodsIn May 2017, 6 ASES patient education b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Importantly, academic orthopedic centers are one of the primary contributors to accurate online information for patients. Expectedly, previous studies have analyzed the readability of educational resources from leading orthopedic organizations 4 , 5 , 11 , 13 , 16 , 20 , 24 and orthopedic academic centers for various pathologies. 15 , 19 However, to the authors’ knowledge, no previous study has investigated the readability of educational materials of academic centers for shoulder arthroplasty.…”
mentioning
confidence: 99%
“…Importantly, academic orthopedic centers are one of the primary contributors to accurate online information for patients. Expectedly, previous studies have analyzed the readability of educational resources from leading orthopedic organizations 4 , 5 , 11 , 13 , 16 , 20 , 24 and orthopedic academic centers for various pathologies. 15 , 19 However, to the authors’ knowledge, no previous study has investigated the readability of educational materials of academic centers for shoulder arthroplasty.…”
mentioning
confidence: 99%
“…A 2014 study compared reading level of the AAOS handouts from 2008 with the revised patient-directed website and found that 84% of web pages remained above the eighth grade reading level ( 20 ). Multiple studies have found the reading level of content provided by professional associations to be higher than recommended by the NIH ( 9 12 , 21 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we copied the content from each handout into a Microsoft Word document and determined reading level by the Flesch-Kincaid reading level. The DISCERN score was one of the first standardized quality indexes for consumer health information and can help categorize information as excellent (63-75), good (51-62), fair (39-50), poor (27-38), and very poor (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) (8,13). The PEMAT Understandability and Actionability tools help measure whether patients with varying levels of health literacy can process information from handouts and whether they are able to act on the information provided.…”
Section: Methodsmentioning
confidence: 99%
“…Using previously described methodology, multiple readability formulae were used to improve the reliability of measures, with scores averaged to form a composite readability score for individual websites (18,(21)(22)(23)(24)(25)(26)(27)(28). A cutoff of an 8th-grade or lower reading level (#8.9 grade level) was chosen to define readability.…”
Section: Readabilitymentioning
confidence: 99%